Paradoxical effects of social media use on workplace interpersonal conflicts - Noreen Kanwal; Ahmad Shahrul Nizam Bin Isha; Rohani Bt Salleh; Nosheen Kanwal; Al-Baraa Abdulrahman Al-Mekhlafi (Cogent Business & Management)
The prevalence of social media use urged researchers to identify its antecedents and consequences. However, research related to social media use in occupational settings has been substantially ignored. Therefore, this study aims to examine the effect of job stress on social media use (social media addiction and work-related social media activities) and its effect on interpersonal conflict at the workplace. The study was conducted using a cross-sectional design. An online questionnaire survey was used to collect data from 253 office employees working in the oil and gas industry in Malaysia. Structural equation modelling was employed for statistical analysis using smart PLS. Results demonstrate a significant positive effect of job stress on social media use (social media addiction and work-related activities on social media) and its significant positive effect on interpersonal conflict in the workplace. Social media behaviour mediates the relationship between job stress and workplace interpersonal conflicts. The study findings show that employees use social media to cope with job stress, which in turn increases interpersonal conflicts at the workplace. Further, the inclination towards social media use indicates the absence of active social support at the workplace. The study findings support the efforts of organisational stakeholders to manage workplace stress by reducing employee’s dependency on online social media and by encouraging “offline active social support” in the offices.